Do we care about built cultural heritage? The empirical evidence based on the Veneto house market - Paolo Rosato; Lucia Rotaris; Margaretha Breil; Valentina Zanatta (Fondazione Eni Enrico Mattei (FEEM), 2008)
Italian historical buildings require urgent and costly maintenance and restoration works, but neither the local, nor the national public administrators can afford these expenditures. Nevertheless the built cultural heritage represent a unique resource of the territory, as it embodies the local social, historical, and cultural values, generates positive externalities (Musgrave, 1959), and stimulates economic activities mainly related to tourism. Is it possible to quantify how much we care about historical buildings and to measure this value in monetary terms? The aim of this paper is to answer to this question via the hedonimetric approach. Specifically, we try to verify if the proximity to historical villas, districts, palaces, squares, fortresses, religious buildings and archeological site systematically influence the house market equilibrium price in the Veneto region (Italy). The paper is organized as follows: in section two a brief review of the literature is reported, in section three the database used for the hedonimetric estimates is described, in section four the econometric models and the results we had obtained are illustrated, and in section five some final comments are drawn.
Keywords: Z1; D62; Q51; 330; Cultural Heritage Externalities; Hedonic Housing Price Method